Prevalence of Haemoproteus and Leucocytozoon spp. in Wild Birds in Hatay, Turkey - Zerek, A; Erdem, I; Alakuş, H; Yaman, M; Altuğ, ME (Journal of the Hellenic Veterinary Medical Society, 2023)
Hemosporidian parasites that cause infections in poultry and death in susceptible animals show a global distribution. In this distribution, the role of infected wild birds migrating among different regions of the world is great. Hatay, where migratory birds enter Turkey, is an active region in terms of vectors, disease agents and hosts. In this study, it was aimed to investigate the prevalence of Haemoproteus and Leucocytozoon parasites in wild birds of Hatay province by microscopic and molecular methods. Blood samples were taken from a total of 50 wild birds belonging to three orders, eight species. On the microscopic examination, Haemoproteus spp. infection 18% (9/50) and mix infection (Haemoproteus spp. and Leucocytozoon spp. ) 4% (2/50) was detected while on the PCR examination, H. columbae 20% (10/50), Leucocytozoon spp. 2% (1/50), mix infection 4% (2/50) was detected. As a result, haemosporidian parasites were detected approximately on one of every four wild birds (microscopic 22%, molecular 26%).